Transcending the Settled Ground: Mapping Obligations of Settler Architects in Canada - Hu, Anita (University of Waterloo, 2026)
This research begins with the recognition that architecture, as both a discipline and a practice, has never been neutral. The design process has long been entangled with histories of colonization, where land was surveyed and transformed into property. In Canada, these processes were instrumental in establishing a settler-colonial relationship to land, one that privileges extraction and productivity over reciprocity and care. This study asks how the architectural design process reproduces these colonial structures and how settler architects might begin to take responsibility for the histories that shape their work. In the outskirts of Sarnia, Ontario, an area known as Chemical Valley sits on the traditional territory of the Chippewa, Odawa, and Potawatomi peoples, collectively known as the Anishinaabeg. It is home to the Aamjiwnaang First Nations reserve and a dense concentration of petrochemical refineries. The term “Chemical Valley” dates back to 1947 as a symbol of national progress, but is now used by Aamjiwnaang First Nations and activists to draw attention to the negative impacts of this industrial corridor. The proximity between the two landscapes exposes how colonial systems of land use and resource extraction persist in shaping environmental and social conditions today. By tracing the evolution of architectural and planning tools, from early land surveys to contemporary zoning and professional standards, this research uncovers how these systems continue to define who has access to land and who bears the burden of its consequences. Through archival analysis and an examination of city planning and architectural practice, this work delineates how the design process itself has been used to legitimize and justify land dispossession. Acts of measuring and drawing are political gestures that determine what is seen, valued, and remembered. Confronting this legacy requires a reorientation of architectural practice, one that shifts toward methods grounded in care and reciprocity, prioritizing relationships with the land.
Keywords: Indigenous; architecture; design process; professional practice; archival research; architectural practice; planning practice; architects; anticolonialism; decolonization